Respuesta :
If this is supposed to be multiplication, this is the answer.
(g*h)(0)
2x(x^2 + 4) =
2x^3 + 8x =
2(0) + 8(0) = 0
If this is supposed to be something else and you forgot the operator between the g and h, let me know and I will redo it for you.
(g*h)(0)
2x(x^2 + 4) =
2x^3 + 8x =
2(0) + 8(0) = 0
If this is supposed to be something else and you forgot the operator between the g and h, let me know and I will redo it for you.
What we do is to substitute to solve.
'(g(h(0)))
g(x) = 2x
g(h(x)) = 2 (x^2 + 4)
(gh)(0) = 2 (0^2 + 4) = 8
'(g(h(0)))
g(x) = 2x
g(h(x)) = 2 (x^2 + 4)
(gh)(0) = 2 (0^2 + 4) = 8